Analisis Iplementasi Aplikasi Juz Amma Berbasis Android menggunakan Adobe Flash Proffesional CS6: Analisis Iplementasi Aplikasi Juz Amma Berbasis Android menggunakan Adobe Flash Proffesional CS6 - Yeni Yuliana; Khana Wijaya (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2021)
Juz Amma is a collection of surahs that exist in the 30th juz in the Koran and is the juz with the highest number of surahs, 37 surahs, but the surah is relatively short. This Juz begins with Sura An 'Naba' and ends with Sura Al Ikhlas, and almost all suras in this juz are classified as Makkiyah (Suras which were revealed before the Prophet moved), as many as 34 suras and the remaining 3 suras namely Al Bayyinah, Al Zalzalah and Surah Surah AN Nashr belongs to the Surah Madaniah (M. Isya Krisnaldi et al, 2018). Education about surahs in juz amma is usually taught using conventional methods such as in schools with the guidance of teachers and at home with the guidance of parents. However, the education delivered by teachers to children in schools, especially in the Nur Baiti Qur'an TPA school as a place of research for writers, is not fully accepted and understood by children at school. Most teachers only use the juz amma book and explain it directly as a guide and explain briefly. So that children feel bored in the learning process with the education delivered by their teacher and cause a lack of enthusiasm in learning and memorizing surahs in juz amma for children. Lack of enthusiasm for learning interest for children is certainly a problem for parents at home, and to increase children's enthusiasm for learning. One of the most popular operating systems today is Android, Android as a linux-based operating system that can be used on various mobile devices / gadgets. Until now android is able to develop more rapidly than its competitors in terms of systems and applications. Therefore, many applications are created based on Android. As will be discussed in this research, the Android-based Juz Amma Application.